Conjoint analysis to understand preferences of contraceptives among women of reproductive age in Ukraine - Mahanova, T.; Tkachenko, N.; Ткаченко, Наталя Олександрівна; Маганова, Тамара Валеріївна (Bulgaria: Sofia, 2021)
This article describes the results of marketing research using conjoint analysis that was conducted to establish the preferences of contraceptives among women of reproductive age in Ukraine to further use the results for effective marketing decisions making in the pharmaceutical industry. It was established that the women`s choice differs significantly depending on their main socioeconomic characteristics: age, income level, and level of education. Priority contraceptives from hormonal, non-hormonal contraceptives, as well as contraceptive medical devices for different age groups of women, was identified. Alfred Marshall’s main economic law was confirmed and the existence of price elasticity according to preferences was established. The results obtained on women’s preferences for certain types of contraceptives will improve the level of compliance, women’s pharmaceutical safety and promote a balance between women’s needs and the capabilities of the contraception supply system.
Keywords: contraceptive; women’s preferences; conjoint analysis